2021
DOI: 10.1111/cogs.12985
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Causal Learning Over Long Timeframes: An Ecological Momentary Experiment Approach

Abstract: The ability to learn cause-effect relations from experience is critical for humans to behave adaptively -to choose causes that bring about desired effects. However, traditional experiments on experiencebased learning involve events that are artificially compressed in time so that all learning occurs over the course of minutes. These paradigms therefore exclusively rely upon working memory. In contrast, in real-world situations we need to be able to learn cause-effect relations over days and weeks, which necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…The reason is that one way in which standard causal-learning paradigms are artificial is that all the trials are presented in quick succession, whereas in the real world (e.g., learning if a medicine is working, or what factors influence sleep), the experiences are spaced out over much longer periods of time. We have found that people can learn true relations between a single cause and a single effect about as well when spaced out one trial per day as when presented rapidly within a few minutes (Willett & Rottman, 2021). Furthermore, in both short and long timeframe conditions, participants incorrectly inferred correlations that did not exist ('illusory correlation') when observing skewed datasets.…”
Section: Longer Delays and Current Studymentioning
confidence: 87%
See 3 more Smart Citations
“…The reason is that one way in which standard causal-learning paradigms are artificial is that all the trials are presented in quick succession, whereas in the real world (e.g., learning if a medicine is working, or what factors influence sleep), the experiences are spaced out over much longer periods of time. We have found that people can learn true relations between a single cause and a single effect about as well when spaced out one trial per day as when presented rapidly within a few minutes (Willett & Rottman, 2021). Furthermore, in both short and long timeframe conditions, participants incorrectly inferred correlations that did not exist ('illusory correlation') when observing skewed datasets.…”
Section: Longer Delays and Current Studymentioning
confidence: 87%
“…Our approach for studying causal learning in more real-world timeframes is to incrementally move towards more and more realistic learning situations. In our first study on learning over a long timeframe, we simply stretched out the standard trial-by-trial paradigm so that one trial occurred each day (Willett & Rottman, 2021). In the current study, we took the next step of introducing delays between the cause and effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is an open question what relationship such radical clock-time shift has on the interactions between human cognition, intervention choice, event abstraction and causal learning. Recent work examining causal inference from observations spanning hours [ 26 ] and days [ 27 ] suggests people have at least as much difficulty identifying relationships and dealing with confounds and dependencies. In such settings it seems likely that processing bottlenecks are caused as much by the structure and limits of long term memory and retrieval as by limited online processing bandwidth.…”
Section: Discussionmentioning
confidence: 99%